Effect of health education using demonstration media for breast self-examination motivation for women in preventing breast cancer - Desy Fadilah Adina Putri; Luh Putu Sri Yuliastuti (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2022)
The number of new breast cancer cases reached 68 thousand (16.6%) of the total 396 thousand new cancer cases in Indonesia. Meanwhile, the number of deaths reached more than 22.000 cases. So with several causal factors and research data on breast cancer, it is only natural that Indonesian women know Breast Self-Examination (BSE) from an early age. BSE is the most recommended early detection of breast cancer for every woman and can be done by yourself. This study aimed to determine the effect of health education with the demonstration method on the BSE motivation of women of childbearing age in preventing breast cancer at the Delima Putih Posyandu, Samapuin Village. The design in this study is a pre-experimental research design. The type used is the One Group Pretest Posttest. The research was conducted at the Delima Putih Posyandu, Samapuin Village, Sumbawa District. The sample in this study was 20 women of childbearing age who were recorded at the Delima Putih Posyandu, Samapuin Village. Data analysis used the Wilcoxon Matched Paired Test. The results showed an effect of health education with the demonstration method on the BSE motivation of women of childbearing age with the Asymp value. Sig 0.000. The result indicates that many women still do not know about BSE, so it is essential to provide education through counseling by midwives or other health workers. Therefore, it is hoped that the role of midwives or other health workers as educators will increase BSE services in the community